Self-efficacy among Classroom, Subject and Special Education Teachers - Saloviita, Timo; Almulla, Abdullah Ahmed (Journal of Ecohumanism, 2024)
Teachers’ self-efficacy beliefs are considered important in determining the success of teachers as educators. This study examines the actual level of teacher self-efficacy, including instructional strategies, classroom management and student engagement, and investigates its relationships with teacher variables of gender, years of experience, teacher category and grade level. The participants comprised 1764 Finnish practicing teachers, including 824 classroom teachers (grades 1–6), 575 subject teachers (grades 7–9) and 365 special education teachers. Teachers’ overall level of self-efficacy was high, but differences existed between teacher categories. Special education teachers scored highest in all dimensions of self-efficacy, while subject teachers scored lowest. Gender differences were found in some subdomains of self-efficacy. Teachers’ self-efficacy showed linear growth with increasing experience. However, a plateau in development was found during the mid-career. Teachers with higher self-efficacy also had a more positive attitude towards inclusive education of students with special educational needs.